Mechanical properties and microstructural evolution of modified 9Cr-1Mo steel after long-term aging for 50,000 h - Baek, Jong-Hyuk; Kim, Sung-Ho; Lee, Chan-Bock; Hahn, Do-Hee (Metals and materials international, 2009)
The mechanical properties and microstructural evolution of modified 9Cr-1Mo steel have been studied to investigate steel property changes after long-term isothermal aging at 600 °C for 50,000 h. The microhardness and strength were maintained constantly after aging but the impact energy was dramatically reduced by 62 % during the aging period. From the viewpoint of microstructural evolution after the aging process, Cr-enrichment and Fe-depletion took place within the M 23 C 6 -type precipitates in the as-aged steel and V-depletion also happened within the VX-type precipitates after aging. In addition, the precipitates of the M 2 Mo-type Laves phase and the segregation of the impurity atoms would be formed during the long-term aging period. It was considered that the sharp reduction of the impact energy could be related to the formation of the Laves phases and the impurity segregation after aging at 600 °C. The phase stability was also verified by the specific heat results up to 950 °C from a DSC test. It was concluded from this study that the modified 9Cr-1Mo steel would keep its microstructural stability at 600 °C during the long-term aging period of 50,000 h, which was equivalent to the in-service life of the SFR fuel cladding.